Study of weight variation and dissolution of Edoxaban split tablets in pharmacy practice - Mantiwee Nimworapan; Sinwisuth Sutheechai; Wanwarang Wongcharoen; Arintaya Phrommintikul; Suntara Eakanunkul (Faculty of Pharmacy, Mahidol University, 2022)
Edoxaban is available in 60 mg, 30 mg, and 15 mg unscored film-coated tablets. Tablet splitting may be an option to reduce medication costs and reduce the country's budget. The objectives of this study were to determine the weight variation and the dissolution profile of the 60 mg edoxaban in split half-tablets using a pill splitter. Thirty edoxaban 60 mg tablets were cut into halves by a right-handed pharmacist. The weight variation of the whole and half tablets were compared. For the dissolution test, 6 whole tablets and 12 half-tablets were separately dissolved in three dissolution media. Sixty half-tablets of edoxaban had the expected half-tablet weight within the 75% to 125% range that fell within the proxy United States Pharmacopeia (USP). The mean total weight of the 1st and 2nd halves were not significantly different from the mean weight of the intact tablets (p-value=0.216). The amount of drug release from the whole and half tablets in 0.1 N HCl medium was greater than 85% in 15 minutes which met the acceptance criteria for the dissolution test. Edoxaban tablets splitting had low variations in weight. Therefore, edoxaban tablets can be split into halves by a tablet cutter.